Captura multimídia em ambientes educacionais instrumentados: aspectos arquiteturais, modelo de comunicação e interface de acesso contextual - Ferreira, Hiran Nonato Macedo (2012)
Capture and access applications support automatic capture of everyday experiences and the subsequent availability of such captured information. These applications explore the concept of ubiquitous computing in order to automate the process of capturing human activities and allow the generation of multimedia documents that can be stored, retrieved, viewed and extended over time. Their development involves the deployment of large and complex computing architectures, aspects of modeling and prototyping, as well as issues regarding storage, retrieval and extension of the captured information. This work presents Classroom eXperience, an infrastructure for capture and access in instrumented educational environments which allows the recording of a series of artifacts produced during a conventional lecture and its subsequent availability to students. The developed infrastructure includes mechanisms for contextual access of captured information, where content recommendations can be made according to the access context of each user. The infrastructure still comprises a peer-to-peer communication model supporting the storage, transfer and replication of captured content. By means of functional prototypes, case studies and qualitative analysis were conducted to evaluate the use of the system.